Pelatihan Peningkatan Keterampilan Mahasiswa dalam Mengembangkan Media Evaluasi Interaktif - Firdiawan Ekaputra (UNIB Press, 2024)
The use of interactive evaluation media in learning is very necessary. This is in order to provide skills to students as prospective teachers to support the implementation of learning and learning media that are favored by students today. The purpose of this training activity is to improve students' skills in developing interactive evaluation media. The participants of the training activities are students of the Chemistry Education Study Program consisting of 21 6th semester students. The training activities for developing interactive evaluation media include the preparation stage of the activity, the implementation stage of the activity, and the evaluation of the activity. Student trainees as prospective teachers need to be equipped with skills that support the implementation of learning and learning media that are favored by students today. The training activities that have been carried out show that students are interested in developing interactive evaluation media to make assessment activities more fun and less rigid.